The Review and Prospect of the Acquisition and Teaching Methods of Phrasal Verbs - Wang, Liu; Chen, Songsong (International Journal of Humanities and Education Development (IJHED), 2020)
The phrasal verb (PV) plays an important role in the English output, but the English learners’ acquisition and usage situation of PVs is not so optimistic. Thus, phrasal verb has always been the hot research topic for the recent years. The previous researches mainly include the current English learners’ usage situation or the avoidance of the phrasal verbs, the factors affecting the acquisition of the phrasal verbs like the social and subjective factors and the linguistic rules, and the different teaching methods of phrasal verbs like the different input and output ways and the combination of input and output ways. All of these aspects are deserved to be studied and concluded to find out more effective methods for phrasal verbs acquisition and teaching. And the combination of cognitive linguistic method and the task-based output method maybe deserved to be tested for the potential advantages of both ways and the research gap.